The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1093/pubmed/fdu049
|View full text |Cite
|
Sign up to set email alerts
|

Associations between parent-reported sleep duration and adiposity in Chinese early adolescents

Abstract: Short sleep duration was associated with higher adiposity indices in early adolescents from China, especially in girls. Interventions focusing on modifying adolescents' sleep habits may potentially prevent obesity and overweight.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 39 publications
(58 reference statements)
3
9
0
Order By: Relevance
“…The mean sleep duration in this study (9.61 h) was very similar to that previously reported in similar aged Chinese children (9.46 h), 14 but the duration in our study was at the low end of that recommended for this age group 21 and lower than that reported for children of similar ages in Western countries. An American study reported a mean sleep duration of 10.15 h in elementary school children (kindergarten through to grade 4), 22 and a Swiss study reported a mean sleep duration of 10.2 h in 10-year-old children.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The mean sleep duration in this study (9.61 h) was very similar to that previously reported in similar aged Chinese children (9.46 h), 14 but the duration in our study was at the low end of that recommended for this age group 21 and lower than that reported for children of similar ages in Western countries. An American study reported a mean sleep duration of 10.15 h in elementary school children (kindergarten through to grade 4), 22 and a Swiss study reported a mean sleep duration of 10.2 h in 10-year-old children.…”
Section: Discussionsupporting
confidence: 89%
“… 13 However, few studies have been conducted on the relationship between more complex sleep characteristics and different obesity indices in China. One study has been undertaken in Shanghai 14 on early adolescents, which found that short sleep duration was associated with higher adiposity indices.…”
Section: Introductionmentioning
confidence: 99%
“…There was also some evidence for gender patterning: with nine of the 103 reviewed articles reporting on sleep duration indicating the association between sleep duration and Ow/Ob as significant among boys only ; while three reported it as significant among girls only; and one reported mixed results across genders, as mentioned above …”
Section: Resultsmentioning
confidence: 90%
“…Overall, there was strong evidence in support of an inverse associa- 44,77,128 ; and one reported mixed results across genders, as mentioned above. 47 Expanded notes on findings can be found in Table S3.…”
Section: Sleep Durationmentioning
confidence: 90%
“…Another cohort study including adolescents found no longitudinal association between sleep duration and body fat percentage in both sexes; however, in the cross-sectional analyses at 17 years a positive association was found among girls only [ 28 ]. Similarly, two cross-sectional studies showed a positive association between sleep duration and body fat percentage in female adolescents only [ 29 , 30 ]. On the other hand, a longitudinal study found no relationship between total sleep and BMI or body fat percentage in either boys and girls [ 31 ].…”
Section: Discussionmentioning
confidence: 93%